The political formation of Brazil and the process of the inertial democracy - Marcello Baquero; Sonia Ranincheski; Henrique Carlos De O. De Castro (Ибероамериканские тетради, 2016)
The article aims to study some important features of the Brazilian political culture. The article focuses on the concept of the “inertial democracy” elaborated by one of its authors, Marcello Baquero. With the purpose to discover the reasons of the disappointment of the Brazilians towards the politics the authors analyze the most signiﬁcant points of the Brazilian political formation and give their conclusions.